Evaluation of the Implementation of Electronic Medical Records (EMR) using the HOT-Fit Method - Diah Prameswari; Ratna Wardani; Agusta Dian Ellina (GLOBAL HEALTH SCIENCE GROUP, 2025)
Implementing Electronic Medical Records (EMR) is a strategic step in improving the efficiency and quality of health services in hospitals. So it is necessary to evaluate the implementation of EMR using the HOT Fit method as a complete solution that best suits the difficulties or limitations currently existing at the Aminah Blitar Islamic Hospital. This research aims to analyze the influence of each variable on the implementation of EMR at the Aminah Blitar Islamic Hospital. The design of this research is a quantitative observational analytic type with a cross-sectional approach. The population of this study is 151 profesional pemberi asuhan (PPA) using EMR. This research uses a proportional random sampling technique. The sample size was determined using the Krejcie and Morgan table and a sample of 108 profesional pemberi asuhan (PPA) using EMR was obtained. The research results show that Service Quality has an effect on User Satisfaction with a significance value of <0.05, namely 0.000. Service Quality influences the Environment with a significance value of <0.05, namely 0.000. User satisfaction does not affect net benefit, with a significance value of> 0.05, 0.357. Environment influences Net-Benefit with a significance value of <0.05, namely 0.000. Service Quality mediated by User Satisfaction has no effect on Net-Benefit with a significance value of > 0.05, namely 0.325. Service Quality with environmental mediation has an effect on Net-Benefit with a significance value of > 0.05, namely 0.0000000. So it can be concluded that the presence of professional and reliable IT personnel supported by government and hospital policies influences the optimal implementation of EMR at the Aminah Blitar Islamic Hospital.